Feed Modification Using Carrot Flour to Improve Growth and Brightness Koi Fish Color - Zaidar, Emma; Sihaloho, Sahat Pangihutan (Talenta Publisher, 2023)
Color is vital in determining the quality of koi fish (Cyprinus carpio L.) and is even seen as an important component in selecting ornamental fish. Therefore, alternative feed sources are needed, which are highly nutritious and increase the brightness of fish. This study aimed to determine the effect of adding carrot flour (Daucus carota L.) and the concentration that had a good impact on increasing the color of Koi fish (Cyprinus carpio L.). This study used six treatments where treatment A was fed containing Spirulina as a control. Treatment B was the addition of carrot flour with a concentration of 5%, C with a concentration of 10%, D with a concentration of 15%, E with a concentration of 20%, and F with a concentration of 25%. The results showed that adding carrot flour affected the brightness of the color of the fish. The best color improvement is found in treatment F, with a value of 6.